2019
DOI: 10.1016/j.ijscr.2019.07.069
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided endoscopic marsupialization technique for frontal sinus mucocele with orbital extension: A case report

Abstract: Highlights Navigated assisted ESS is a safe treatment for FM with orbital extension. A navigation support could avoid an external approach. The image-guided system could be useful if bony landmarks are missing. The image-guided system could be useful if orbital erosion is present. Navigated assisted ESS could completely drain lateral and multi-cystic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
1
6
0
1
Order By: Relevance
“…Although all the reviewed studies [14]- [20] in addition to our study show successful results with recurrence rates at or close to 0%. Nevertheless, it should be emphasized that long term follow-up time is necessary for mucoceles.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Although all the reviewed studies [14]- [20] in addition to our study show successful results with recurrence rates at or close to 0%. Nevertheless, it should be emphasized that long term follow-up time is necessary for mucoceles.…”
Section: Discussionsupporting
confidence: 53%
“…A good number of published case series and case reports has shown that endoscopic marsupialization has become the approach of choice in the majority of patients attaining a satisfactory clinical outcome and a lower rate of recurrence [14]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…IGS with an imaging update provided by an intraoperative cone‐beam (or volume) CT scanner has been associated with an alteration of the surgical plan in 30% of ESS cases 2116,2117 . Furthermore, IGS also has specific uses for frontal sinus surgery, 2118 orbital surgery, 2107,2119,2120 sphenoidotomy, 2121 skull base surgery, 2122 pediatric sinus surgery, 2123–2125 procedures with skull base erosion, 2126 trephination procedures, 2127 device placement, 2128 orbital surgery, 2107 mucocele marsupialization, 2129 and osteoplastic frontal sinus surgery 2130–2132 …”
Section: Surgery For Chronic Rhinosinusitismentioning
confidence: 99%
“…The use of navigation can further enhance the precision of the surgery in difficult circumstances such as distorted sinus anatomy or a revision sinus surgery making the procedure safer and further reducing patient morbidity. [ 11 12 ] However, the benefit of its application in all procedures requires further evaluation because of its high-cost factor.…”
Section: Onclusionmentioning
confidence: 99%